How Impact Investing Firms Are Responding to Sustain and Grow Social Economy Enterprises in Light of the COVID-19 Pandemic - Islam, SM; Habib, A (Elsevier BV, 2022)
The COVID-19-induced disruptions have hardest hit social economy enterprises. While impact investing is considered a promising vehicle to stimulate and grow social economy enterprises, little is known about how impact investors are actually responding to sustain and grow social economy enterprises amidst the COVID-19 pandemic. We find that impact investors sacrifice additional financial returns in pandemic-focused impact investments where they see the potential for attaining significantly higher than usual social impact by protecting hundreds of vulnerable social economy enterprises and beneficiaries amidst the pandemic. We also find that guarantees are introduced as an innovative impact investment instrument to tackle the pandemic, although they have remained heavily underutilized. Furthermore, debt instruments tend to dominate in pandemic-focused impact investments. Finally, in response to the pandemic, impact investors emphasize developing and strengthening a supportive social impact ecosystem to protect both portfolio and non-portfolio social economy enterprises and their beneficiaries. We also explain how the impact investing market has evolved during pandemic times and how it might evolve post-pandemic to support social economy enterprises.
Keywords: Impact investing; Social economy enterprise; COVID-19 pandemic; Impact-return trade-off; Social impact ecosystem